2014
DOI: 10.1111/jnc.12675
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the physiological function of the β‐amyloid precursor protein: beyond Alzheimer's disease

Abstract: The β-amyloid precursor protein (APP) has been extensively studied for its role as the precursor of the β-amyloid protein (Aβ) of Alzheimer's disease. However, the normal function of APP remains largely unknown. This article reviews studies on the structure, expression and post-translational processing of APP, as well as studies on the effects of APP in vitro and in vivo. We conclude that the published data provide strong evidence that APP has a trophic function. APP is likely to be involved in neural stem cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
161
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 219 publications
(167 citation statements)
references
References 203 publications
3
161
1
2
Order By: Relevance
“…For example, APP is expressed in developing neuroblasts at the time of cell proliferation and differentiation (26,31,41). In the present study we found that in the absence of APP, there was a decrease in NSPC differentiation into neurons.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…For example, APP is expressed in developing neuroblasts at the time of cell proliferation and differentiation (26,31,41). In the present study we found that in the absence of APP, there was a decrease in NSPC differentiation into neurons.…”
Section: Discussionsupporting
confidence: 60%
“…Emerging evidence suggests that APP plays a role in neuronal growth and neural repair, although the precise mechanisms have been unclear (31). The expression of APP is regulated developmentally (28,32) and is increased in association with neurite outgrowth and synaptogenesis (8,26).…”
Section: Discussionmentioning
confidence: 99%
“…PME-1 and LCMT-1 bidirectionally altered both the electrophysiological and behavioral responses to nanomolar Aβ administration, without affecting baseline LTP, behavioral performance, or the ability of the administration of 200 pM Aβ to enhance LTP. Given that normal physiological levels of Aβ play an important role in regulating neuronal activity (35,(42)(43)(44), this ability to target Aβ's pathological actions selectively could provide an approach that reduces AD-related impairments without interfering with normal nervous system function. Identifying the molecules acting downstream of PP2A in this process also will help clarify the molecular mechanisms by which Aβ exerts its pathological effects.…”
Section: Discussionmentioning
confidence: 99%
“…Эта точка зрения подтверждается данными [26], показывающими, что со-вместное удаление генов APP и APLP2, либо двух APLP, либо всех трех членов семейства приводит к ранней пост-натальной смерти. Экспериментальные данные показы-вают, что APP играет важную роль в процессах клеточного роста и пролиферации, а также может служить трофиче-ским фактором, влияя на рост отростков нейронов (ней-риты) и синаптогенез [27].…”
Section: роль аβ в патогенезе баunclassified